Fluktuasi Populasi Walang Sangit Leptocorisa oratorius F. (Hemiptera : Alydidae) Pada Komunitas Padi Di Dusun Kepitu, Sleman, Daerah Istimewa Yogyakarta - Pratimi, Anita - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2011)
Research on population fluctuation of rice bug L. oratorius on paddy community using Situ Bagendit,Ciherang and IR64 rice varieties in Kepitu Village, Sleman was done. This experiment was conducted in April 2011to July 2011 in the paddy community Kepitu Village, Sleman, Daerah Istimewa Yogyakarta. The objectives of theresearch was to predict the population fluctuation of rice bug pest in rice crops in paddy community Kepitu Village,Sleman, Daerah Istimewa Yogyakarta with a special approach using correlogram analysis.The purposive sampling technique was used in this research. Rice terraces of the sampling unit were plotted inrice varieties of Situ Bagendit, Ciherang and IR64 respectively. Rice bug was counted in series of periodical time(every three days). Total number of rice bug per m2 was used for determining the serial correlation coefficient (rs)and the variance of log population density at time t and t +1 (log Nt and log Nt+1) for every three days (t).The valueof rs was associated with s in correlogram. Fluctuation population of the rice bug determined through concistencyperiodicity and amplitude curve of the correlogram. The population distribution pattern was identified by means theratio between variance and the average of total number of rice bug.The result showed that the population fluctuation of rice bug was predicted by the migration, from thereservoir to rice crop and vice versa. The plots which were adjacent to refuge protected from insecticide sprays havehigher abundance of rice bug than the plots which were located far from the refuge. Based on the correlationcoefficient, the population fluctuation of Situ Bagendit rice’s plots has an oscillation trend. The corellogram curveshowed exogenous and irregular type. In the plots planted with Ciherang rice, the pop fluctuation was alsoexperience oscillations with corellogram curve shapes, it indicates endogenous and exogenous type with an irregularperiodicity. In the plots planted with IR64 rice, oscillation occur with the endogenous corellogram curve with nonstationaryand non-periodict type. The pattern of population distribution of rice bug in Kepitu Village was aclustered distribution.